Prevalence of prehypertension in young adults in a semi-urban district in Telangana - Rao, Kande V. Mallikarjuna; Reddy, G. Pavan Kumar (International Journal of Advances in Medicine, 2017)
Background: Referred to as silent killer, is one of the leading causes of cardiovascular diseases. The risk of cardiovascular disease in people with prehypertension increases with the increase in burden of the other risk factors such as obesity, diabetes mellitus and dyslipidaemia. This study was undertaken to estimate the prevalence of prehypertension among the young adults in our area. Methods: 2658 patients, between 18-35 years of age, were included in the study. Complete physical and clinical examination, blood pressure, blood tests for cholesterol levels, blood glucose levels, and triglyceride levels were done. BMI, waist to hip ratio was also calculated. Results: 1433 (53.9%) of the patients were females and 1225 (46.1%) were males. Pre hypertension was found in 846 (31.8%) hypertension in 261(9.8%) young adults. There was a higher rate of BMI, blood glucose levels and cholesterol in these patients. Conclusions: There is a high prevalence of prehypertension among the young adults in our geographical. Therefore, awareness among the community, lifestyle modifications such as proper nutrition and less of fatty foods, regular check-ups especially for those with risk factors and timely treatment are very essential for curbing outcomes such as cardiovascular diseases.